PROFITABILITY, CORPORATE SOCIAL RESPONSIBILITY DICLOSURE AND GOOD CORPORATE GOVERNANCE - Ardila, Isna; Sembiring, Masta (CV. Radja Publika, 2022)
Testing and assessing the effect of Corporate Social Responsibility Disclosure and Good Corporate Governance (GCG) on profitability in companies engaged in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2016 – 2019 using a sample of 60 is the purpose of the study. Samples were taken using purposive sampling method and the data sources used were secondary data in the form of financial statements and company annual reports. Hypothesis testing shows that there is no effect of Corporate Social Responsibility Disclosure on profitability and there is a significant effect of Good Corporate Governance on profitability.